Transmission electron microscopy on as–deposited and freestanding single crystalline Fe70Pd30 ferromagnetic shape memory alloy thin film. (15th July 2017) - Landgraf, A.; Lotnyk, A.; Mayr, S.G.
Abstract: Within this transmission electron microscopy study, we explore the atomic structure of Fe-Pd thin films with and without supporting single crystalline (001) MgO substrate. We observe a phase structural transition depending strongly on spatial limited stresses. While around the film-substrate interface edge dislocations form to minimize stresses due to the lattice misfit between MgO and Fe-Pd, preferring the face-centered cubic phase, upper sample regions show twinning structures with the face- and body-centered tetragonal phase, respectively. In freestanding films, bct and bcc phases are observed. Compared to unprocessed lift-off films, no hierarchical structure was existent anymore, based on changed stress distributions. Graphical Abstract: